2020
DOI: 10.1038/s41427-020-0207-x
|View full text |Cite
|
Sign up to set email alerts
|

Strain-induced stripe phase in charge-ordered single layer NbSe2

Abstract: Charge density waves are ubiquitous phenomena in metallic transition metal dichalcogenides. In NbSe2, a trigonal 3×3 structural modulation is coupled to a charge modulation. Recent experiments reported that a trigonal-stripe transition occurred at the surface, possibly due to local strain and/or accidental doping. We employ ab-initio calculations to investigate the structural instabilities arising from strain in a pristine single layer and analyze the energy hierarchy of the structural and charge modulations. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…[26][27][28] Strain-induced phase separation between 3 triangular and stripe phases in charge-ordered 1H-NbSe2 monolayer has been explored by ab initio calculations. [29] Compared with the bulk of 2H polymorph of NbSe2 and TaSe2, CDW instability can be strongly enhanced in the monolayer limit. [30,31] By contrast, the CDW order of bulk 2H-TaS2 vanishes in the 2D limit, accompanied with substantial enhancements of the superconductivity, indicating competition between CDW order and superconductivity down to the monolayer limit.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Strain-induced phase separation between 3 triangular and stripe phases in charge-ordered 1H-NbSe2 monolayer has been explored by ab initio calculations. [29] Compared with the bulk of 2H polymorph of NbSe2 and TaSe2, CDW instability can be strongly enhanced in the monolayer limit. [30,31] By contrast, the CDW order of bulk 2H-TaS2 vanishes in the 2D limit, accompanied with substantial enhancements of the superconductivity, indicating competition between CDW order and superconductivity down to the monolayer limit.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Similarly, experimental studies have shown that strain affects the relative stability of various CDWs. 41,42 A recent study has also found that impurities in NbS 2 may induce CDW patterns around them, which may be incommensurate with the CDW patterns around other impurities. 14 Here, we computationally studied whether a small quantity of Re dopants can stabilize CDWs in NbS 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It is also known that the stability of CDWs in NbSe 2 is sensitive to small changes made to the system. For example, computational studies have indicated that Na-intercalation suppresses CDWs, and the adsorptions of Co, Mn, K, and Ga unveil CDW configurations not found in the pristine material. , Similarly, experimental studies have shown that strain affects the relative stability of various CDWs. , A recent study has also found that impurities in NbS 2 may induce CDW patterns around them, which may be incommensurate with the CDW patterns around other impurities …”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, the heavily electron-doped monolayer NbSe 2 also hosts a 2×2 CDW order [41]. Ab initio calculations have established the modulated crystal structure of the triangular 3a 0 [42][43][44] and stripe 4a 0 [45] CDW phases of monolayer 2H-NbSe 2 , but the crystal structure of the 2×2 CDW is not known. Due to the wide application of NbSe 2 [23,46] and the important role of substrate strain in monolayer materials, it is crucial to understand the structural ground state and electronic properties of this phase.…”
Section: Introductionmentioning
confidence: 99%